Main-duct intraductal papillary mucinous neoplasm: high cancer risk in duct diameter of 5 to 9 mm - Hackert, Thilo; Fritz, Stefan; Klauß, Miriam; Bergmann, Frank; Hinz, Ulf; Strobel, Oliver; Schneider, Lutz; Büchler, Markus W. (Annals of surgery, 2015)
Objective: - The 2012 international consensus guidelines for the management of intraductal papillary mucinous neoplasms (IPMN) recommend surgical treatment in main-duct IPMN patients with a main pancreatic duct (MPD) diameter of ≥10 mm. Aim of the present study was to analyze cancer risk in patients with an MPD diameter of less than 10 mm. - Methods: - All consecutive patients (prospective data protocol) with histological proof of IPMN who underwent surgery between January 2004 and December 2013 were included in the study. Clinical characteristics, particularly preoperative imaging with regard to morphology of the MPD, were correlated with final histopathology. - Results: - Among a total of 605 patients who underwent surgery for IPMN, there were 320 patients with MPD involvement, 238 patients with mixed-type IPMN, and 82 patients with main-duct IPMN alone. The total malignancy rate including high-grade dysplasia and invasive carcinoma in IPMNs with MPD involvement was 68%. When the MPD diameter was 5 to 9 mm, malignancy rate was 59%, whereas in MPD diameter more than 10 mm, it was 73%. No statistical correlations were observed between MPD diameter and clinical and/or IPMN features such as age, cyst location, mural nodules, serum tumor markers, or bilirubin. - Conclusions: - Main-duct IPMNs with a MPD between 5 and 9 mm already bear a significant risk of malignancy. Therefore, surgical treatment is clearly indicated in patients with a MPD diameter of ≥5 mm and the 2012 guidelines should be discussed and adapted with regard to this topic.
Gesehen am 23.02.2021